The Phenomenon of Child Marriage: Between Socioreligious Problem and The Impact of Digitalization - Islami, Prima Yustitia Nurul (UIN Sunan Ampel Surabaya, 2023)
Child marriage is a social problem that needs to be resolved. West Java is one region with the highest rate of child marriage. In 2020, Based on the data of Women's Empowerment and Protection of West Java Province, there were 9,821 child marriages. Child marriage on Basically, it still occurs in all villages in Bogor Regency. During the pandemic Covid, the rate of child marriage has increased, and post-pandemic these conditions have not changed much. The phenomenon of child marriage in the village of Pagelaran, South Cianjur happen in three changing periods is interesting to capture in this study. This research uses a qualitative approach with methods Participatory Action Research (PAR) a method that involves subject research since the beginning of this research activity. The subject of this research is a young mother aged 15 to 25 years who lives in the village of Pagelaran, South Cianjur. The number of informants was determined using the Snowball method. Data collection uses field observation, PAR, in-depth interviews, and studies literature. This research found that several factors cause child marriage, but religion is one of the main factors in child marriage in Pagelaran Village. Apart from that, there are push factors and pull factors that cause child marriage to continue to occur. Apart from that, digitalization is also an important cause of child marriage today. One of them is caused by the influence of globalization and lack of parental supervision which causes the potential for child marriage due to unwanted pregnancies.